STEREODYNAMICS OF PHOTON-INDUCED REACTIONS VIA DOPPLER-RESOLVED LASER-INDUCED FLUORESCENCE SPECTROSCOPY - PHOTODISSOCIATION OF HONO2 AND THE REACTION OF O((1)D) WITH CH4 - Brouard, M; Duxon, S; Enriquez, P; Simons, J (1993)
The application of polarised, Doppler-resolved laser-induced fluorescence (LIF) probing of the products scattered from photon-induced 'half-collision' (photodissociation) and 'full-collision' (bimolecular reaction) processes is developed to include the velocity dependence of their stereodynamics. Fourier-transform inversion procedures are used to derive the products' speed distributions W(v′) and vector correlations βij(v′) (a) in the photodissociation of HONO2 and (b) in the bimolecular reaction of O(1D) with CH4. In the former example, they provide new insight into the stereodynamics of the photodissociation, HONO2 + hν → HO(v = 0, N) + NO2(X̃, Ã) In the latter, together with newly developed LAB → CM simulation methods, they provide new insight into the stereodynamics of the reaction, O(1D) + CH4 → OH(v = 4, N) + CH3 The OH is shown to be generated with its rotational angular momentum j′, constrained to lie in a plane directed perpendicular to its centre-of-mass relative velocity, k′.